2008
DOI: 10.1111/j.1750-3841.2008.00830.x
|View full text |Cite
|
Sign up to set email alerts
|

New Phenylethanoid Glycosides and Sugar Esters from Ku‐Ding‐Cha, a Herbal Tea Produced from Ligustrum purpurascens

Abstract: Ku-Ding-Cha is a kind of herbal tea used commonly in China for its effects on hypertension, fatness, inflammation, and diuresis. The chlorophyll removal fraction from 60% aqueous acetone extract of Ku-Ding-Cha produced from the leaves of Ligustrum purpurascens (Oleaceae) exhibited observable antioxidant activity on 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay (SC50 = 45 microg/mL). Further detailed phytochemical investigation on this fraction led to the isolation of 2 new phenylethanoid glycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 19 publications
(20 reference statements)
2
21
0
Order By: Relevance
“…The IC 50 values for L. morrisonense, L. liukiuense, L. pricei, L. sinense, and L. lucidum in the DPPH assay were 0.48, 0.94, 1.38, 1.47, and 2.06 mg/ml, respectively. The results obtained from the DPPH assay is similar to recent reports of other Ligustrum species, including L. lucidum and L. robustum (Chen, Wong, Leung, He, & Huang, 2002;Katsube et al, 2004;Nagy et al, 2006;She, Wang, Zeng, Yang, & Zhang, 2008;Zhu et al, 2009). For the TEAC assay, the IC 50 values for L. morrisonense, L. liukiuense, L. pricei, L. sinense, and L. lucidum were 0.21, 0.24, 0.37, 0.52, and 1.40 mg/ml, respectively.…”
Section: Antioxidant and Radical-scavenging Activity Of Ligustrum Leavessupporting
confidence: 87%
“…The IC 50 values for L. morrisonense, L. liukiuense, L. pricei, L. sinense, and L. lucidum in the DPPH assay were 0.48, 0.94, 1.38, 1.47, and 2.06 mg/ml, respectively. The results obtained from the DPPH assay is similar to recent reports of other Ligustrum species, including L. lucidum and L. robustum (Chen, Wong, Leung, He, & Huang, 2002;Katsube et al, 2004;Nagy et al, 2006;She, Wang, Zeng, Yang, & Zhang, 2008;Zhu et al, 2009). For the TEAC assay, the IC 50 values for L. morrisonense, L. liukiuense, L. pricei, L. sinense, and L. lucidum were 0.21, 0.24, 0.37, 0.52, and 1.40 mg/ml, respectively.…”
Section: Antioxidant and Radical-scavenging Activity Of Ligustrum Leavessupporting
confidence: 87%
“…The fourteen known phenylethanoid glycosides were identified as acteoside (1) (He et al, 1992), ligupurpuroside A (3) (He et al, 1992), syringalide A 3 0 -a-L-rhamnopyranoside (4) (Zhang et al, 2013), lipedoside A-I (5) (He et al, 1994), kankanoside G (6) (Yoshikawa et al, 2006), lipedoside A-II (7) (He et al, 1994), isoacteoside (8) (Lu and Shen, 2008), osmanthuside B (9) (He et al, 1992), ligupurpuroside C (10) (She et al, 2008), cis-lipedoside A-I (11) (He et al, 1992), ligurobustoside N (12) (He et al, 2003), (E)-ligupurpuroside B (13) (He et al, 1992), angoroside A (14) (Li et al, 2011), and (Z)-ligupurpuroside B (15) (Wong et al, 2001) by comparison of their spectroscopic data with those reported in the literature.…”
Section: Resultsmentioning
confidence: 98%
“…The leaves of L. purpurascens have long been used as a traditional Chinese tea known as Ku-Ding-Cha (He et al, 1992). Phytochemical investigations have revealed that the main chemical constituents of this plant are flavonoids, monoterpenoids, iridoids and phenylethanoid glycosides (He et al, 1992;He et al, 2003;Wong et al, 2001;She et al, 2008;Tian et al, 1998Tian et al, , 1997Li et al, 2010;Tian and Sun, 1999;Tian et al, 1996;Xiong et al, 2007). Among them, phenylethanoid glycosides exhibited antioxidative and immunomodulatory activities, while iridoids showed antiviral properties (Wong et al, 2001;He et al, 2003;She et al, 2008;Song et al, 2012;Ma et al, 2001).…”
Section: Introductionmentioning
confidence: 96%
“…1C). In these spectra, the parent ions and product ions of these five constituents were compared with literature (Li et al, 2010She et al, 2008). The structures Table 2 Effects of CPGs on mouse peritoneal MF phagocytosis of chicken RBCs and NK cell activity.…”
Section: The Analyzed Constituents and The Content Of Major Glycosidementioning
confidence: 99%